Synthesis and Characterization of 3-S-impurities in Timolol Maleate - Zhou, Dejun; Wang, Keyang; Zhang, Yuying; Liu, Xiaoyue; Mao, Xiaoxia (Current Organic Synthesis, 2025)
BackgroundTimolol maleate is clinically used for the treatment of hypertension, angina pectoris, tachycardia, and glaucoma.ObjectiveThe aim of this study was to enhance the safe use of timolol maleate and investigate a synthesis method for 3-S-timolol, a newly identified impurity in timolol API (Active Pharmaceutical Ingredients).Methods(S)-3-(tert-butylamino)propane-1,2-diol (1) was used as a raw material. 3-S-timolol maleate (7) was synthesized through a five-step reaction. Overall yield was 57.7%, with a purity of 98%.ResultsThe structure of the target compound was confirmed via analysis of its 1H nuclear magnetic resonance, 13C nuclear magnetic resonance, and high-resolution mass spectrometry spectra.ConclusionThe synthesis method was straightforward and yielded a high-purity product suitable for use as a reference in the analysis and identification of timolol maleate-related substances.
Keywords: β-adrenergic receptor blocker